2015
DOI: 10.1142/s0129183116500170
|View full text |Cite
|
Sign up to set email alerts
|

Three-band decomposition analysis in multiscale FSI models of abdominal aortic aneurysms

Abstract: Computational modeling plays an important role in biology and medicine to assess the e®ects of hemodynamic alterations in the onset and development of vascular pathologies. Synthetic analytic indices are of primary importance for a reliable and e®ective a priori identi¯cation of the risk. In this scenario, we propose a multiscale°uid-structure interaction (FSI) modeling approach of hemodynamic°ows, extending the recently introduced three-band decomposition (TBD) analysis for moving domains. A quantitative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The rationale is the important link between the MBDA technique and the notion of wall shear stress gradient (WSSG). In particular, the WSSG is implicitly defined as a spatiotemporal quantity related with the fluid motion (Cherubini et al 2015) and the generalized MBDA technique has been shown to gain much information with respect to the usual synthetic indicators (Nestola et al 2015(Nestola et al , 2016. On these bases, in the context of cardiac dynamics, which is analogously a spatiotemporal problem, we foresee the application of an extended MBDA for the definition of novel clinical synthetic risk indicators for the predictive identification of pathological situations eventually evolving into sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is the important link between the MBDA technique and the notion of wall shear stress gradient (WSSG). In particular, the WSSG is implicitly defined as a spatiotemporal quantity related with the fluid motion (Cherubini et al 2015) and the generalized MBDA technique has been shown to gain much information with respect to the usual synthetic indicators (Nestola et al 2015(Nestola et al , 2016. On these bases, in the context of cardiac dynamics, which is analogously a spatiotemporal problem, we foresee the application of an extended MBDA for the definition of novel clinical synthetic risk indicators for the predictive identification of pathological situations eventually evolving into sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Rawi and Al-Jumaily 10 studied abdominal aorta narrowing using computational fluid dynamics and found that arterial blockage in excess of 20% of the diameter significantly influences the pressure wave and reduces the systolic blood pressure at the right femoral artery. Nestola et al 11 performed simulation for abdominal aortic aneurysms, bringing attention to three-band decomposition methodology for analysis of moving domains. The importance of shunt angulations as a determinant of shear-stress-induced thrombosis was proposed by Celestin et al, 12 who analyzed characteristics of blood flow from central aorta to pulmonary artery.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on CAs based on the FSI approach focuses on the calculation of WSS, while specific statements on circumferential wall stress are omitted or discussed secondary [144][145][146]. The same observation can be made for research on early AAA development [147]. In both, solid structure computation is primarily used to simulate the influence of wall deformation on the fluid and therefore supersede the boundary condition of a rigid wall.…”
Section: The Traction Must Be At Equilibriummentioning
confidence: 99%